A composite welding sheet and its preparation method and application

By using diamond-reinforced brazing sheets and composite welding sheets with multi-layer metal layer structures in semiconductor devices, the problems of high cost and thermal conductivity attenuation in the prior art are solved, efficient thermal conductivity and high temperature stability are achieved, and production costs are reduced .

CN119216862BActive Publication Date: 2025-02-18CAI LUN ADVANCED SEMICONDUCTOR MATERIALS (CHONGQING) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411755568.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-18
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The silver and indium used in the prior art are relatively high-priced metal materials, resulting in an increase in cost; the thermal conductivity of its bonded semiconductor devices will be severely attenuated after long-term service, which cannot meet the needs of automotive-grade high-power device packaging.

Method used

The composite welding sheet, including diamond-reinforced brazing sheet and multi-layer metal layer structure, is used to form an efficient conductive and thermally conductive structure through mixing and hot pressing sintering of doped modified diamond powder and titanium powder.

Benefits of technology

It improves the thermal conductivity and high temperature stability of semiconductor devices, reduces the overall thermal expansion coefficient of the solder layer, enhances the mechanical strength and reliability of the solder sheet, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119216862B_ABST
    Figure CN119216862B_ABST
Patent Text Reader

Abstract

The present invention relates to a composite welding sheet and a preparation method and application thereof. The composite welding sheet comprises a diamond-reinforced copper welding sheet, a first metal layer to a fifth metal layer sequentially arranged in a direction away from the surface of the diamond-reinforced copper welding sheet, a second metal layer and a fourth metal layer are copper layers, a third metal layer is a tin layer, and a fifth metal layer is a silver layer. The diamond-reinforced copper welding sheet is formed by mixing nano-scale copper powder, micron-scale doped modified diamond powder and titanium powder and then hot-pressing. The present invention performs doping modification on micron diamond, which can allow doped atoms to penetrate into the micron diamond lattice, improve the electrical conductivity, reduce the heating power of the welding layer, improve the thermal conductivity and thermal conductivity stability, and control the generated intermetallic compound to be the required Cu6Sn5 by controlling the thickness ratio of the second metal layer to the third metal layer and the thickness ratio of the fourth metal layer to the third metal layer, and prevent the generation of brittle Cu3Sn, thereby improving the mechanical strength and reliability of the metal-to-metal joint on the basis of achieving weldability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductors, and in particular relates to a composite welding sheet and a preparation method and application thereof. Background Art

[0002] As electronic devices continue to develop towards miniaturization, high integration, high temperature resistance, high service reliability and high power density, higher reliability requirements are placed on the welding of high-power devices. Traditional high-lead solders (such as tin / lead alloy solders, tin / lead / silver alloy solders) have low melting points, poor thermal conductivity, and are harmful to the human body and the environment. They are difficult to meet the high-temperature service requirements of the new generation of wide bandgap semiconductor devices and are gradually being eliminated.

[0003] The transient liquid interconnection process is a liquid-assisted sintering process used to form interconnections between metal or metallization layer surfaces. The principle of forming interconnections is based on the phase transition caused by the metallurgical reaction between the low-melting-point metal components (such as Ga, Sn, In and their alloys) and the high-melting-point metal components in the system. After heating to melting, the low-melting-point metal components and the high-melting-point substrates on both sides (such as Al, Cu, Ag, etc.) form a high-temperature stable phase at a lower temperature through diffusion reaction, thereby realizing permanent interconnection of the substrates. Compared with the plastic interconnection method, the joints obtained by TLP technology do not have a weakened area of ​​the structure, and the sintering temperature is much lower than the remelting temperature of the parent material, which can further reduce the thermal impact. The transient liquid interconnection process is suitable for high-temperature service environments and has the advantages of low-temperature preparation and high-temperature use.

[0004] For example, the patent document with publication number CN112204731A discloses a silver-indium transient liquid phase method for bonding semiconductor devices and heat sinks, and a semiconductor structure with a silver-indium transient liquid phase bonding joint. The solution utilizes an ultra-thin silver-indium transient liquid phase bonding joint formed between the semiconductor device and the heat sink, which can minimize its thermal resistance to achieve high thermal conductivity, fully realize the heat dissipation capacity of the heat sink, and thus enable high-power electronic devices and optoelectronic devices to achieve their optimal performance. However, the silver and indium used in the solution are both relatively expensive metal materials, which will increase costs in large-scale promotion and are not conducive to large-scale industrial production; secondly, the thermal conductivity (such as thermal resistance) of the bonded semiconductor device will be severely attenuated after long-term service, and cannot meet the requirements of automotive-grade high-power device packaging. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a composite welding sheet and its preparation method and application, so as to solve the technical problems that silver and indium used in the prior art are relatively high-priced metal materials, which will increase costs during large-scale promotion; secondly, the thermal conductivity (such as thermal resistance) of the joined semiconductor devices will seriously decay after long-term service, and cannot meet the requirements of automotive-grade high-power device packaging.

[0006] To achieve the above object, the technical solution of the present invention is as follows:

[0007] In a first aspect, the present invention provides a composite welding sheet, comprising a diamond-reinforced copper welding sheet, a first metal layer to a fifth metal layer sequentially arranged in a direction away from the surface of the diamond-reinforced copper welding sheet, the second metal layer and the fourth metal layer are copper layers, the third metal layer is a tin layer, and the fifth metal layer is a silver layer, and the diamond-reinforced copper welding sheet is formed by mixing nano-scale copper powder, micron-scale doped modified diamond powder and titanium powder and then hot pressing.

[0008] Optionally, the diamond-reinforced copper welding sheet has a thickness of 30-120 μm, preferably 40-120 μm.

[0009] Optionally, the thickness of the first metal layer is 20-100 nm.

[0010] Optionally, the second metal layer has a thickness of 220-500 nm.

[0011] Optionally, the thickness of the third metal layer is 100-250 nm.

[0012] Optionally, the fourth metal layer has a thickness of 220-500 nm.

[0013] Optionally, a thickness ratio of the second metal layer to the third metal layer is not greater than 2.24:1.

[0014] Optionally, a thickness ratio of the fourth metal layer to the third metal layer is not greater than 2.24:1.

[0015] Optionally, the fifth metal layer has a thickness of 500-1000 nm.

[0016] Optionally, the first metal includes at least one of zinc, titanium, zirconium, nickel and bismuth.

[0017] Optionally, the particle size of the nano-scale copper powder is 10-500 nm, preferably 20-300 nm.

[0018] Optionally, the particle size of the titanium powder is 0.2-20 μm, preferably 1-20 μm.

[0019] Optionally, the micron-sized doped and modified diamond powder is obtained by doping and modifying micron diamond, and the doping element is selected from at least one of boron, sulfur, nitrogen, phosphorus and magnesium.

[0020] Optionally, the particle size of the micron diamond is 1-50 μm, preferably 5-50 μm.

[0021] In the present application, when the doping element is boron, the boron source used includes but is not limited to: boron element, boron oxide, trimethyl borate and other substances.

[0022] Optionally, when sulfur is used as the dopant, the sulfur source used includes but is not limited to: sulfur dioxide, hydrogen sulfide, dimethyl disulfide and other substances.

[0023] Optionally, when the doping element is nitrogen, the nitrogen source used includes but is not limited to: nitrogen, ammonia, ammonium chloride, melamine, and hexamethylenetetramine.

[0024] Optionally, when phosphorus is used as the doping element, the phosphorus source used includes but is not limited to: phosphine and other substances.

[0025] Optionally, when magnesium is used as the doping element, the magnesium source used includes but is not limited to: magnesium nitride, magnesium boride and other substances.

[0026] Optionally, the mass ratio of the nano-scale copper powder, the micron-scale doped modified diamond powder and the titanium powder is 94-99: 0.5-5.0: 0.5-1.0, preferably 95-99: 0.5-5.0: 0.5-1.0.

[0027] In a second aspect, the present invention also provides a method for preparing the composite welding sheet as described above, comprising the following steps:

[0028] S1. doping and modifying the micron diamond to obtain micron-sized doped modified diamond powder;

[0029] S2. Mix the micron-sized doped modified diamond powder and titanium powder, grind to obtain a composite powder, mix the nano-sized copper powder and the composite powder, pickle, dry, and hot press to obtain a diamond-enhanced copper solder sheet

[0030] S3. In an oxygen-free environment, a first metal layer, a second metal layer, a third metal layer, a fourth metal layer and a fifth metal layer are sequentially grown on the surface of the diamond-enhanced copper welding sheet to obtain the composite welding sheet.

[0031] Optionally, in step S1, during the doping modification process, the temperature is 80-1100°C, preferably 90-1100°C; and the pressure is 8-15 kPa, preferably 9-15 kPa.

[0032] Optionally, in step S2, the grinding speed is 150-500 rpm, preferably 200-500 rpm; the grinding time is 4-10 h, preferably 5-10 h.

[0033] Optionally, in step S2, the pickling solution is dilute hydrochloric acid or formic acid.

[0034] Optionally, in step S2, when the pickling solution is dilute hydrochloric acid, the concentration range is 3%-30%, preferably 5%-15%.

[0035] Optionally, in step S2, when the pickling solution is formic acid, the concentration range is 3%-15%, preferably 3%~10%.

[0036] Optionally, in step S2, the vacuum drying temperature is 50-80°C, preferably 50-60°C.

[0037] Optionally, in step S2, the temperature of the hot pressing is 250-600°C, preferably 300-600°C; the pressure of the hot pressing is 10-50MPa, and the duration of the hot pressing is 5-30min.

[0038] Optionally, in step S3, the first metal layer is grown by physical vapor deposition.

[0039] Optionally, in step S3, the second metal layer is grown by physical vapor deposition.

[0040] Optionally, in step S3, the third metal layer is grown by physical vapor deposition.

[0041] Optionally, in step S3, the fourth metal layer is grown by physical vapor deposition.

[0042] Optionally, in step S3, the fifth metal layer is grown by physical vapor deposition.

[0043] Optionally, in step S3, during the growth of the first metal layer, the sputtering power is 150-400 W, preferably 150-350 W; and the gas pressure is 0.1-5 Pa.

[0044] Optionally, in step S3, during the growth of the second metal layer, the sputtering power is 120-400 W, preferably 200-320 W; and the gas pressure is 0.1-5 Pa.

[0045] Optionally, in step S3, during the growth of the third metal layer, the sputtering power is 10-50 W, preferably 15-50 W; and the gas pressure is 0.1-5 Pa.

[0046] Optionally, in step S3, during the growth of the fourth metal layer, the sputtering power is 120-400 W, preferably 200-320 W; and the gas pressure is 0.1-5 Pa.

[0047] Optionally, in step S3, during the growth of the fifth metal layer, the sputtering power is 80-400W, preferably 180-300W; and the gas pressure is 0.1-5Pa.

[0048] In a third aspect, the present invention also provides a semiconductor device, which includes a metal substrate and a semiconductor chip, wherein the metal substrate and the semiconductor chip are connected together by a composite welding sheet as described above or a composite welding sheet prepared according to the method as described above and sintered in a reducing atmosphere.

[0049] In a fourth aspect, the present invention also provides a method for preparing the semiconductor device as described above, comprising the following steps:

[0050] The composite welding sheet is placed on a metal substrate, a semiconductor chip is attached to the surface of the composite welding sheet, and sintering is performed in a reducing gas atmosphere to obtain the semiconductor device.

[0051] Optionally, the reducing gas is selected from hydrogen, formic acid or a mixture of the two.

[0052] Optionally, the ratio of the surface area of ​​the solder pad to the surface area of ​​the semiconductor chip is 0.8-1:1, preferably 0.95-1:1.

[0053] Optionally, the reducing gas is selected from hydrogen, formic acid or a mixture of the two.

[0054] Optionally, the sintering temperature is 200-380° C., preferably 220-280° C.; the sintering time is 0.5-5 min, preferably 1-5 min.

[0055] As described above, the composite welding sheet and its preparation method and application of the present invention have the following beneficial effects:

[0056] In the present invention, by doping and modifying the micron diamond, doping atoms such as boron, sulfur, nitrogen, phosphorus, and magnesium can be infiltrated into the micron diamond lattice, which helps to improve the electrical conductivity, reduce the heating power of the solder layer (i.e., the composite solder sheet), and thus improve the thermal conductivity and thermal conductivity stability of the semiconductor device.

[0057] In the present invention, by mixing and grinding micron-sized doped modified diamond powder with titanium powder, the diamond and titanium powder can be more fully contacted and mixed, and the bonding force between the diamond and titanium powder is increased, so that a tighter interface bonding between titanium and copper is formed in the subsequent sintering process, the tightness of the interface bonding is improved, the thermal conductivity is improved, and the mechanical strength, thermal conductivity and high-temperature stability of the semiconductor device solder layer are improved.

[0058] In the present invention, by controlling the content of micron-sized doped modified diamond powder in the mixed powder at a specific level, the thermal conductivity of the semiconductor device can be significantly improved while maintaining the same order of magnitude of conductivity of the overall solder layer compared to pure silver / copper metal, and the difference in thermal expansion coefficient between the solder layer and the semiconductor chip can be reduced, thereby comprehensively improving the high-temperature stability of the semiconductor device.

[0059] In the present invention, the composite powder is mixed with nano-copper powder and then pickled, cleaned and vacuum dried to remove oxidized metals (such as copper oxide, cuprous oxide and titanium oxide) in the powder, thereby improving the thermal and electrical conductivity of the manufactured semiconductor device.

[0060] In the present invention, the mixed powder is sintered into a diamond-reinforced copper solder sheet through hot pressing treatment. Under hot pressing conditions, the porosity of the solder sheet can be controlled within 1%, thereby improving the thermal conductivity and high-temperature stability of the semiconductor device.

[0061] In the present invention, by growing the first metal layer on the surface of the diamond-enhanced copper soldering sheet in an oxygen-free environment, the transformation of β-Sn can be suppressed, thereby improving the thermal conductivity and high-temperature stability of the semiconductor device.

[0062] In the present invention, by growing a second metal layer copper layer, a third metal layer tin layer, a fourth metal layer copper layer and a fifth metal layer silver layer on the surface of the first metal layer in an oxygen-free environment, and maintaining the thickness of each layer at the nanometer scale, the solderability of the soldering pad under low temperature and low pressure can be achieved, the silver layer can form an intermetallic compound with the solderable metal layer on the surface of the chip and the lead frame, and the semiconductor chip-soldering pad-lead frame can be interconnected.

[0063] In the present invention, by controlling the thickness ratio of the second metal layer to the third metal layer and the thickness ratio of the fourth metal layer to the third metal layer, the generated intermetallic compound is controlled to be the desired Cu 6 Sn 5 , to prevent the formation of brittle Cu 3 Sn, on the basis of achieving weldability, improves the mechanical strength and reliability of metal-to-metal joints.

[0064] The present invention reduces the overall thermal expansion coefficient of the solder layer (i.e., the composite solder sheet), reduces the thermal stress between the semiconductor chip and the solder layer during temperature changes, and thereby improves the thermal conductivity and high-temperature stability of the semiconductor device.

[0065] The present invention can improve the mechanical strength, thermal conductivity and high-temperature stability of semiconductor devices.

[0066] The raw material cost adopted by the method of the present invention is low, and invalid or scrapped diamond semiconductor chips or electrode materials can be reused, which have a wide source and reduce the production cost.

[0067] The method of the present invention is applicable to mainstream production equipment in the field of semiconductor packaging. No pressure is required during the chip sintering process, and the soldering sheets can be customized and cut according to the chip area and substrate area, which is conducive to realizing industrialized batch production. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 A flow chart of a method for preparing a semiconductor device of the present invention;

[0069] Figure 2 It is a schematic diagram of the structure of the composite welding sheet of the present invention. DETAILED DESCRIPTION

[0070] The present invention is further described below through specific examples, but it should be pointed out that the specific material ratios, process conditions and results described in the embodiments of the present invention are only used to illustrate the present invention and cannot be used to limit the scope of protection of the present invention. All equivalent changes or modifications made according to the spirit of the present invention should be included in the scope of protection of the present invention.

[0071] An embodiment of the present invention provides a composite welding sheet, which includes a diamond-reinforced copper welding sheet with a thickness of 30-120 μm, a first metal layer to a fifth metal layer sequentially arranged in a direction away from the surface of the diamond-reinforced copper welding sheet, the thickness of the first metal layer is 20-100 nm, the thickness of the second metal layer and the fourth metal layer is 220-500 nm, the thickness of the third metal layer is 100-250 nm, the thickness of the fifth metal layer is 500-1000 nm, the thickness ratio of the second metal layer to the third metal layer is not greater than 2.24:1, the thickness ratio of the fourth metal layer to the third metal layer is not greater than 2.24:1, the first metal includes at least one of zinc, titanium, zirconium, nickel and bismuth, the second metal and the fourth metal are copper, the third metal is tin, and the fifth metal is silver;

[0072] The diamond-enhanced copper welding sheet is made by mixing nano-copper powder with a particle size of 10-50nm, micron-sized doped modified diamond powder and titanium powder with a particle size of 0.2-20μm in a mass ratio of 94-99:0.5-5.0:0.5-1.0, and then hot pressing and sintering.

[0073] The micron-sized doped modified diamond powder is prepared by doping and modifying micron diamond, and the doping element is selected from at least one of boron, sulfur, nitrogen, phosphorus and magnesium.

[0074] Another embodiment of the present invention provides a method for preparing the composite welding sheet as above, comprising the following steps:

[0075] S1. doping and modifying the micron diamond to obtain micron-sized doped modified diamond powder;

[0076] S2. Mixing micron-sized doped modified diamond powder and titanium powder, grinding at a speed of 150-500 rpm for 4-10 hours to obtain a composite powder, mixing the nano-sized copper powder and the composite powder, pickling, vacuum drying at a temperature of 50-80 ° C, and hot pressing at 250-600 ° C and 10-50 MPa for 5-30 minutes to obtain a diamond-enhanced copper solder sheet;

[0077] S3. In an oxygen-free environment, a first metal layer, a second metal layer, a third metal layer, a fourth metal layer and a fifth metal layer are sequentially grown on the surface of the diamond-enhanced copper solder sheet to obtain a composite solder sheet;

[0078] Growing the first metal layer by physical vapor deposition at a sputtering power of 150-400 W and a gas pressure of 0.1-5 Pa;

[0079] Growing a second metal layer by physical vapor deposition at a sputtering power of 120-400 W and a gas pressure of 0.1-5 Pa;

[0080] Growing the third metal layer by physical vapor deposition at a sputtering power of 10-50W and a gas pressure of 0.1-5Pa;

[0081] Growing a fourth metal layer by physical vapor deposition at a sputtering power of 120-400 W and a gas pressure of 0.1-5 Pa;

[0082] The fifth metal layer is grown by physical vapor deposition at a sputtering power of 80-400W and a gas pressure of 0.1-5Pa.

[0083] Another embodiment of the present invention provides a semiconductor device, including a metal substrate and a semiconductor chip, wherein the metal substrate and the semiconductor chip are connected together through a composite welding sheet after sintering in a reducing atmosphere, and the surface area ratio of the first metal layer to the semiconductor chip is 0.8-1:1.

[0084] Another embodiment of the present invention provides a method for preparing the semiconductor device as described above, comprising the following steps:

[0085] Placing the composite solder sheet on a metal substrate, attaching a semiconductor chip to the surface of the composite solder sheet, and sintering at 200-380° C. for 0.5-5 minutes in a reducing gas atmosphere to obtain a semiconductor device;

[0086] The reducing gas is preferably selected from hydrogen, formic acid or a mixture of the two.

[0087] The present invention is described in detail below by specific examples. It should also be understood that the following examples are only used to specifically illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values ​​​​exemplified below.

[0088] Example 1

[0089] according to Figure 1 The process shown is used to prepare a semiconductor device, and the specific steps are as follows:

[0090] S1. Boron doping modification of micron diamond with a particle size of 10 μm was performed at a temperature of 1000°C and a pressure of 8 kPa (the boron source was gaseous trimethyl borate) to obtain micron-sized doped modified diamond powder;

[0091] S2. Mix micron-sized doped modified diamond powder and titanium powder with a particle size of 5 μm in a mass ratio of 5:1, place in a ball mill, vacuum and mill at a speed of 500 rpm for 4 hours to obtain a composite powder, mix nano-sized copper powder with a particle size of 50 nm and the composite powder in a mass ratio of 97:3, place in a hydrochloric acid solution with a temperature of 35°C and a concentration of 10wt%, ultrasonically clean for 5 minutes, then ultrasonically clean in anhydrous ethanol for 3 times (each time for 8 minutes), then place in a vacuum oven at 50°C and dry for 30 minutes, then introduce the dried powder into a mold and hot press under vacuum conditions of a temperature of 400°C and a pressure of 20MPa for 10 minutes to obtain a diamond-reinforced copper solder sheet with a thickness of 50 μm;

[0092] S3. Place the diamond-enhanced copper solder sheet in a magnetron sputtering device, and in an argon atmosphere, sequentially grow a first metal layer titanium layer with a thickness of 50 nm (sputtering power of 300 W and gas pressure of 3 Pa), a second metal layer copper layer with a thickness of 336 nm (sputtering power of 250 W and gas pressure of 1 Pa), a third metal layer tin layer with a thickness of 150 nm (sputtering power of 30 W and gas pressure of 1 Pa), a fourth metal layer copper layer with a thickness of 336 nm (sputtering power of 250 W and gas pressure of 1 Pa), and a fifth metal layer silver layer with a thickness of 800 nm (sputtering power of 200 W and gas pressure of 1 Pa) on the front and back sides of the diamond-enhanced copper solder sheet to obtain a composite solder sheet (structure as shown in FIG. Figure 2 As shown, the main layer refers to the diamond-reinforced copper solder sheet);

[0093] Obviously, the thickness ratio of the second metal layer to the third metal layer is 336nm:150nm=2.24:1, and the thickness ratio of the fourth metal layer to the third metal layer is 336nm:150nm=2.24:1;

[0094] S4. Cut the composite solder sheet into a size of 5mm*5mm*0.18mm, which is 95% of the surface area of ​​the SiC MOSFET chip (i.e., the ratio of the composite solder sheet to the semiconductor area is 0.95:1), i.e., cut into 4.88mm*4.88mm*0.18mm;

[0095] S5. Place the cut composite solder sheet on a copper substrate, attach a semiconductor chip to the surface of the cut composite solder sheet, and sinter for 2 minutes at a pressure of 5 MPa in a hydrogen atmosphere at a temperature of 280° C. to obtain a semiconductor device.

[0096] Example 2

[0097] according to Figure 1 The process shown is used to prepare a semiconductor device, and the specific steps are as follows:

[0098] S1. Nitrogen doping modification (nitrogen source is ammonia) of micron diamond with a particle size of 10 μm is performed at a temperature of 950°C and a pressure of 10 kPa to obtain micron-sized doped modified diamond powder;

[0099] S2. Mix micron-sized doped modified diamond powder and titanium powder with a particle size of 1 μm in a mass ratio of 4:1, place in a ball mill, vacuum and mill at a speed of 500 rpm for 4 hours to obtain a composite powder, mix nano-sized copper powder with a particle size of 50 nm and the composite powder in a mass ratio of 95:5, place in a formic acid solution with a temperature of 40°C and a concentration of 10wt%, ultrasonically clean for 5 minutes, then ultrasonically clean twice in anhydrous ethanol (each time for 10 minutes), then place in a vacuum oven at 50°C and dry for 30 minutes, then introduce the dried powder into a mold and hot press for 10 minutes under vacuum conditions at a temperature of 350°C and a pressure of 15MPa to obtain a diamond-reinforced copper solder sheet with a thickness of 80 μm;

[0100] S3. Place the diamond-enhanced copper solder sheet in a magnetron sputtering device, and sequentially grow a first metal layer titanium layer with a thickness of 50 nm (sputtering power of 250 W and gas pressure of 1 Pa), a second metal layer copper layer with a thickness of 400 nm (sputtering power of 300 W and gas pressure of 5 Pa), a third metal layer tin layer with a thickness of 200 nm (sputtering power of 20 W and gas pressure of 5 Pa), a fourth metal layer copper layer with a thickness of 400 nm (sputtering power of 300 W and gas pressure of 5 Pa), and a fifth metal layer silver layer with a thickness of 600 nm (sputtering power of 250 W and gas pressure of 5 Pa) on the front and back sides of the diamond-enhanced copper solder sheet to obtain a composite solder sheet (whose structure is as shown in FIG. Figure 2 As shown, the main layer refers to the diamond-enhanced copper solder sheet);

[0101] Obviously, the thickness ratio of the second metal layer to the third metal layer is 400nm:200nm=2:1, and the thickness ratio of the fourth metal layer to the third metal layer is 448nm:200nm=2.24:1;

[0102] S4. Cut the composite solder sheet into a size of 8mm*8mm*0.18mm, which is 98% of the surface area of ​​the SiC MOSFET semiconductor chip (i.e., the ratio of the composite solder sheet to the semiconductor area is 0.98:1), i.e., cut into 7.92mm*7.92mm*0.18mm;

[0103] The cut composite solder sheet is placed on a substrate, a semiconductor chip is attached to the surface of the cut composite solder sheet, and the semiconductor device is manufactured by sintering the semiconductor chip for 5 minutes at a temperature of 300° C. and a pressure of 3 MPa in a hydrogen atmosphere.

[0104] Comparative Example 1

[0105] A semiconductor device was prepared in the same manner as in Example 1 except for the following conditions:

[0106] S2. Diamond with a particle size of 10-50μm and titanium powder with a particle size of 5μm were mixed in a mass ratio of 5:1, placed in a ball mill, vacuumized and ball-milled at a speed of 500rpm for 4h to obtain a composite powder, and nano-copper powder with a particle size of 50nm and the composite powder were mixed in a mass ratio of 97:3, placed in a hydrochloric acid solution with a temperature of 35°C and a concentration of 10wt%, ultrasonically cleaned for 5min, and then ultrasonically cleaned in anhydrous ethanol for 3 times (each time for 8min), and then placed in a vacuum oven at 50°C for 30min, and then the dried powder was introduced into a mold and hot pressed under vacuum conditions of a temperature of 400°C and a pressure of 20MPa for 10min to obtain a diamond-reinforced copper solder sheet with a thickness of 50μm.

[0107] That is, the micron diamond was not doped and modified in this comparative example.

[0108] Comparative Example 2

[0109] A semiconductor device was prepared in the same manner as in Example 1 except for the following conditions:

[0110] S2. Place the micron-sized doped modified diamond powder in a ball mill, evacuate the ball mill at a speed of 500rpm for 4 hours to obtain a composite powder, mix the nano-sized copper powder with a particle size of 50nm and the micron-sized doped modified diamond powder in a mass ratio of 97:3, place it in a hydrochloric acid solution with a temperature of 35°C and a concentration of 10wt%, ultrasonically clean it for 5 minutes, then ultrasonically clean it in anhydrous ethanol for 3 times (each time for 8 minutes), then place it in a vacuum oven at 50°C and dry it for 30 minutes, then introduce the dried powder into a mold and hot press it under vacuum conditions at a temperature of 400°C and a pressure of 20MPa for 10 minutes to obtain a diamond-reinforced copper solder with a thickness of 50μm.

[0111] That is, no titanium powder was added in this comparative example.

[0112] Comparative Example 3

[0113] A semiconductor device was prepared in the same manner as in Example 1 except for the following conditions:

[0114] S2. Mix micron-sized doped modified diamond powder and titanium powder with a particle size of 5 μm in a mass ratio of 5:1 to obtain a composite powder; mix nano-sized copper powder with a particle size of 50 nm and the composite powder in a mass ratio of 97:3, place it in a hydrochloric acid solution with a temperature of 35°C and a concentration of 10wt%, and ultrasonically clean it for 5 minutes. Then, ultrasonically clean it in anhydrous ethanol for 3 times (each time for 8 minutes), and then place it in a vacuum oven at a temperature of 50°C and dry it for 30 minutes. Then, introduce the dried powder into a mold and hot press it under vacuum conditions of a temperature of 400°C and a pressure of 20 MPa for 10 minutes to obtain a diamond-reinforced copper solder sheet with a thickness of 50 μm.

[0115] That is, in this comparative example, the composite powder and the nano-copper powder were mixed without ball milling.

[0116] Comparative Example 4

[0117] A semiconductor device was prepared in the same manner as in Example 1 except for the following conditions:

[0118] S2. Mix micron-scale doped modified diamond powder and titanium powder with a particle size of 5μm in a mass ratio of 5:1, place in a ball mill, evacuate and ball-mill at a speed of 500rpm for 4 hours to obtain a composite powder, mix nano-scale copper powder with a particle size of 50nm and the composite powder in a mass ratio of 97:3, place in a hydrochloric acid solution with a temperature of 35°C and a concentration of 10wt%, ultrasonically clean for 5 minutes, then ultrasonically clean in anhydrous ethanol for 3 times (each time for 8 minutes), then place in a vacuum oven at 50°C and dry for 30 minutes, then introduce the dried powder into a mold and hot press under vacuum conditions of a temperature of 400°C and a pressure of 20MPa for 10 minutes to obtain a diamond-reinforced copper solder sheet with a thickness of 50μm.

[0119] That is, in this comparative example, the nano-copper powder and the composite powder were mixed without being washed.

[0120] Comparative Example 5

[0121] A semiconductor device was prepared in the same manner as in Example 1 except for the following conditions:

[0122] S3. Place the diamond-reinforced copper solder sheet in a magnetron sputtering device, and in an argon atmosphere, sequentially grow a second metal layer copper layer with a thickness of 336 nm (the sputtering power is 250 W and the gas pressure is 1 Pa), a third metal layer tin layer with a thickness of 150 nm (the sputtering power is 30 W and the gas pressure is 1 Pa), a fourth metal layer copper layer with a thickness of 336 nm (the sputtering power is 250 W and the gas pressure is 1 Pa), and a fifth metal layer silver layer with a thickness of 800 nm (the sputtering power is 200 W and the gas pressure is 1 Pa) on the front and back sides of the diamond-reinforced copper solder sheet to obtain a composite solder sheet.

[0123] That is, in this comparative example, the first metal layer is not grown on the surface of the diamond-reinforced copper solder sheet.

[0124] Comparative Example 6

[0125] A semiconductor device was prepared in the same manner as in Example 1 except for the following conditions:

[0126] S3. Place the diamond-reinforced copper solder sheet in a magnetron sputtering device, and in an argon atmosphere, sequentially form a first metal layer titanium layer with a thickness of 50 nm (sputtering power of 300 W and gas pressure of 3 Pa), a second metal layer copper layer with a thickness of 500 nm (sputtering power of 250 W and gas pressure of 1 Pa), a third metal layer tin layer with a thickness of 150 nm (sputtering power of 30 W and gas pressure of 1 Pa), a fourth metal layer copper layer with a thickness of 500 nm (sputtering power of 250 W and gas pressure of 1 Pa), and a fifth metal layer silver layer with a thickness of 800 nm (sputtering power of 200 W and gas pressure of 1 Pa) on the front and back sides of the diamond-reinforced copper solder sheet to obtain a composite solder sheet.

[0127] Obviously, the thickness ratio of the second metal layer to the third metal layer is 500nm:150nm=10:3, and the thickness ratio of the fourth metal layer to the third metal layer is 500nm:150nm=10:3.

[0128] That is, the thickness ratio of the second / fourth metal layer to the third metal layer in this comparative example is greater than 2.24:1.

[0129] Performance Testing

[0130] The shear strength, thermal resistance and thermal resistance attenuation rate of the solder layers of the semiconductor devices prepared in Examples 1-2 and Comparative Examples 1-6 after a 20,000-cycle (6 min / cycle) power cycle test were tested, and the results are shown in Table 1.

[0131] Among them, the shear strength test method is: using a universal testing machine to test the shear strength, the shear rate is 1mm / min;

[0132] The thermal resistance detection method is: first calibrate the temperature sensitivity coefficient (i.e., K coefficient) of the chip through the K coefficient, and then calibrate the thermal resistance through the K coefficient. The parameters in the process of calibrating the temperature sensitivity coefficient (i.e., K coefficient) of the chip through the K coefficient are set as follows: the maximum value of the maximum current and the maximum value of the voltage drop are the standard rated value or the maximum value in the data sheet, the minimum current is -100mA, VGS (on) is 15V, VGS (OFF) is -5V, the temperature rise range is 25℃ to 85℃, and every 20℃ is a point, and the K coefficient can be obtained;

[0133] The parameters in the process of calibrating thermal resistance by K coefficient are as follows: import K coefficient, set transient heating current to 1 / 5 of rated current, set heating and cooling time to 150s, and then the thermal resistance can be obtained;

[0134] The resistivity test method is to place the weld layer sample on the test platform at room temperature, ensure that the four probes are in good contact with the sample surface, pass a constant current, and measure the voltage drop according to the formula Calculate the resistivity of the welding layer (U is the voltage drop, S is the cross-sectional area of ​​the sample, I is the current, and L is the length of the sample);

[0135] The steps for detecting the thermal resistance decay rate are as follows: perform a load power cycle test for 20,000 times under the conditions of a power-on time of 2 minutes, a cooling time of 4 minutes, and a temperature difference of 100°C. After the test, detect the thermal resistance again according to the above method, and then calculate the thermal resistance decay rate according to the formula: Thermal resistance decay rate = (thermal resistance before the test - thermal resistance after the test) / thermal resistance before the test * 100%.

[0136] Table 1 Test results

[0137]

[0138] As shown in Table 1, compared with Comparative Example 1 (micron diamond is not doped and modified), the solder layer resistivity, solder layer thermal resistance and thermal resistance attenuation rate of Example 1 (micron diamond is doped and modified) are significantly reduced. This result shows that in the present invention, by doping and modifying micron diamond, doping atoms such as boron, sulfur, nitrogen, phosphorus and magnesium can be infiltrated into the micron diamond lattice, which helps to improve the electrical conductivity, reduce the heat generation power of the solder layer (i.e., the composite solder sheet), and thus improve the thermal conductivity and thermal conductivity stability of the semiconductor device.

[0139] As shown in Table 1, compared with Comparative Example 2 (no titanium powder added), the shear strength of Example 1 (titanium powder added) increased significantly, and the resistivity, thermal resistance and thermal resistance attenuation rate of the welding layer decreased significantly; compared with Comparative Example 3 (no ball milling after mixing the composite powder and nano-copper powder), the shear strength of Example 1 (ball milling after mixing the composite powder and nano-copper powder) increased significantly, and the resistivity, thermal resistance and thermal resistance attenuation rate of the welding layer decreased significantly. The results show that the present invention can make the diamond and titanium powder more fully contact and mix by mixing and grinding the micron-level doped modified diamond powder with titanium powder, increase the bonding force between diamond and titanium powder, thereby forming a tighter interface bonding between titanium and copper in the subsequent sintering process, improving the tightness of the interface bonding, improving the thermal conductivity, and thus improving the mechanical strength, thermal conductivity and high temperature stability of the welding layer of the semiconductor device.

[0140] As shown in Table 1, compared with Comparative Example 4 (the nano-copper powder and the composite powder are mixed without washing), the solder layer resistivity and thermal resistance attenuation rate of Example 1 (the nano-copper powder and the composite powder are mixed and then washed) are significantly reduced. This result shows that the present invention removes the oxidized metal (such as copper oxide, cuprous oxide, titanium oxide) in the powder by mixing the composite powder with the nano-copper powder, then pickling, washing, and vacuum drying, thereby improving the thermal conductivity of the semiconductor device.

[0141] As shown in Table 1, compared with Comparative Example 5 (the first metal layer is not grown on the surface of the diamond-enhanced copper solder sheet), the solder layer resistivity and thermal resistance attenuation rate of Example 1 (the first metal layer is grown on the surface of the diamond-enhanced copper solder sheet) are significantly reduced. This result shows that the present invention can inhibit the conversion of β-Sn by growing the first metal layer on the surface of the diamond-enhanced copper solder sheet in an oxygen-free environment, thereby improving the thermal conductivity and high-temperature stability of the semiconductor device.

[0142] As shown in Table 1, compared with Comparative Example 6 (the thickness ratio of the second metal layer to the third metal layer is greater than 2.24:1, and the thickness ratio of the fourth metal layer to the third metal layer is greater than 2.24:1), the shear strength of Example 1 (the thickness ratio of the second metal layer to the third metal layer is not greater than 2.24:1, and the thickness ratio of the fourth metal layer to the third metal layer is not greater than 2.24:1) is improved, and the thermal resistance decay rate is significantly reduced. This result shows that the present invention controls the thickness ratio of the third metal layer to the second metal layer and the thickness ratio of the third metal layer to the fourth metal layer (the thickness ratio of the second metal layer to the third metal layer does not exceed 2.24:1, and the thickness ratio of the fourth metal layer to the third metal layer does not exceed 2.24:1), and the generated intermetallic compound is controlled to be the desired Cu 6 Sn 5 , to prevent the formation of brittle Cu 3 Sn, on the basis of achieving weldability, improves the mechanical strength and reliability of metal-to-metal joints.

[0143] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A composite welding sheet, characterized in that: The composite welding sheet comprises a diamond-reinforced copper welding sheet, a first metal layer to a fifth metal layer sequentially arranged in a direction away from the surface of the diamond-reinforced copper welding sheet, the second metal layer and the fourth metal layer are copper layers, the third metal layer is a tin layer, and the fifth metal layer is a silver layer. The diamond-reinforced copper welding sheet is formed by mixing nano-scale copper powder, micron-scale doped modified diamond powder and titanium powder and then hot-pressing. The thickness of the diamond-enhanced copper welding sheet is 30-120 μm; The thickness of the first metal layer is 20-100 nm; The thickness of the second metal layer is 220-500 nm; The thickness of the fourth metal layer is 220-500 nm; The thickness of the third metal layer is 100-250nm; The thickness ratio of the second metal layer to the third metal layer is not greater than 2.24:1; The thickness ratio of the fourth metal layer to the third metal layer is not greater than 2.24:1; The thickness of the fifth metal layer is 500-1000nm; The first metal includes at least one of zinc, titanium, zirconium, nickel, and bismuth.

2. The composite welding sheet according to claim 1, characterized in that: The particle size of the nano copper powder is 10-500nm; And / or, the particle size of the titanium powder is 0.2-20 μm.

3. The composite welding sheet according to claim 1, characterized in that: The micron-sized doped and modified diamond powder is prepared by doping and modifying micron diamond, and the doping element is selected from at least one of boron, sulfur, nitrogen, phosphorus and magnesium; And / or, the mass ratio of the nano-scale copper powder, the micron-scale doped modified diamond powder and the titanium powder is 94-99: 0.5-5.0: 0.5-1.

0.

4. The method for preparing the composite welding sheet according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. doping and modifying the micron diamond to obtain micron-sized doped modified diamond powder; S2. mixing the micron-sized doped modified diamond powder and titanium powder, grinding to obtain a composite powder, mixing the nano-sized copper powder and the composite powder, pickling, drying, and hot pressing to obtain a diamond-enhanced copper solder sheet; S3. In an oxygen-free environment, a first metal layer, a second metal layer, a third metal layer, a fourth metal layer and a fifth metal layer are sequentially grown on the surface of the diamond-enhanced copper solder sheet to obtain the composite solder sheet.

5. The method for preparing the composite welding sheet according to claim 4, characterized in that: In step S2, the grinding speed is 150-500 rpm, and the grinding time is 4-10 hours; And / or, in step S2, the drying temperature is 50-80°C; And / or, in step S2, the temperature of the hot pressing is 250-600°C, the pressure of the hot pressing is 10-50 MPa, and the duration of the hot pressing is 5-30 min.

6. The method for preparing a composite welding sheet according to claim 4, wherein in step S3, the first metal layer is grown by physical vapor deposition; and / or, in step S3, growing the second metal layer by physical vapor deposition; and / or, in step S3, growing the third metal layer by physical vapor deposition; and / or, in step S3, growing the fourth metal layer by physical vapor deposition; And / or, in step S3, the fifth metal layer is grown by physical vapor deposition.

7. The method for preparing the composite welding sheet according to claim 4, characterized in that: In step S3, during the growth of the first metal layer, the sputtering power is 150-400 W and the pressure is 0.1-5 Pa; And / or, in step S3, during the growth of the second metal layer, the sputtering power is 120-400 W and the vacuum degree is 0.1-5 Pa; And / or, in step S3, during the growth of the third metal layer, the sputtering power is 10-50 W and the vacuum degree is 0.1-5 Pa; And / or, in step S3, during the growth of the fourth metal layer, the sputtering power is 120-400 W and the vacuum degree is 0.1-5 Pa; And / or, in step S3, during the growth of the fifth metal layer, the sputtering power is 80-400W and the vacuum degree is 0.1-5Pa.

8. A semiconductor device, characterized in that: The semiconductor device comprises a metal substrate and a semiconductor chip, wherein the metal substrate and the semiconductor chip are connected together by sintering in a reducing atmosphere through a composite welding sheet as described in any one of claims 1 to 3 or a composite welding sheet prepared by a method as described in any one of claims 4 to 7.

9. The method for preparing a semiconductor device according to claim 8, wherein: The following steps are involved: The composite welding sheet is placed on a metal substrate, a semiconductor chip is attached to the surface of the composite welding sheet, and sintering is performed in a reducing gas atmosphere to obtain the semiconductor device.

Citation Information

Patent Citations

  • Silver-indium transient liquid phase method of bonding semiconductor device and heat-spreading mount and semiconductor structure having silver-indium transient liquid phase bonding joint

    CN112204731A

  • Flake diamond-reinforced metal matrix composite and preparation method

    CN105220049A